Education in human peoples rights and racial justice in the movement of migrants from Sub-Saharan Africa in Brazil and Argentina - VARGEM, Alex; VISOTSKY , Jessica (Utopía y Praxis Latinoamericana, 2023)
This work recovers the perspective of racial justice from Afro-Latin American studies to delve into the pedagogical praxis in human rights from the perspective of human rights and peoples, within the migrant movements of sub-Saharan Africa, in Brazil and Argentina. We develop the research from qualitative perspectives, oral history, collaborative ethnographies and participatory research, views that allow us to propose the processes of co-investigation or co-construction of knowledge together with the subjects themselves who suffer rights violations and who fight for justice. racial. Among the results of the research we can point out the need to assume intersectional perspectives to understand and explain oppressions, the need also to assume perspectives that make the approach to pedagogical processes more complex in order to develop initiatives from the movements themselves and accompanying public policies or restitution of rights.